Artificial Intelligence and Financial Auditing in Morocco: Towards a Redefinition of Practices and Skills - SAAD-ALLAH , Imane; ELOUIDANI, Abdelkbir (African Scientific Journal, 2025)
Abstract : This article explores the impact of artificial intelligence (AI) on financial auditing, particularly its influence on auditor practices and skills. Using qualitative methodology, we conducted semi-structured interviews with industry professionals to identify challenges, opportunities and expectations related to integrating AI into audit processes. The results reveal a gradual transformation of auditing practices, marked by the automation of repetitive tasks, improved efficiency and the need for auditors to develop new technical skills. However, concerns related to the impact of AI on the integrity of professional judgments and the continuing education of auditors have emerged. The study highlights the importance of training auditors so that they can fully exploit AI tools while preserving the ethics and rigor of the profession. Keywords : artificial intelligence, financial audit, challenges, opportunities, efficiency.